Effective microorganisms on the development of green cabbage - Oliveira, Juliana Elias de; Richardson Sales; Silva, Josimar Aleixo da; Tosta, Diego Souza; Merson, Adriano Azevedo; Gravina, Geraldo de Amaral; Lima, Wallace Luís de (Comunicata Scientiae, 2024)
The cabbage culture has economic importance for small farmers, being one of the most consumed vegetables in Brazil, which demands more sustainable and low-cost technologies for its cultivation. Thus, the objective of this work was to analyze the influence of fertilization with biofetilizer enriched with effective microorganisms (EM) on the development of green cabbage (Brassica oleracea var. capitata.) in agroecological production management. The experimental design was in randomized blocks with four treatments: (T1 – 0.0%; T2 – 5.0% (0.25 L of inoculated solution for 5 L of dechlorinated mineral water); T3 - 10% (0. 5 L of inoculated solution to 5 L of dechlorinated mineral water) and T4 – 20% (0.75 L of inoculated solution to 5 L of dechlorinated mineral water) and 5 replications. Traits of growth, development and production were evaluated. The data were submitted to analysis of variance and linear regression. The characteristics circumference, longitudinal diameter, transversal diameter, marketable fresh mass, total fresh mass, nitrogen content, protein and moisture showed significant effects in response to EM doses. In general, the regression model with the best fit was the quadratic, with the maximum points close to the 10% dose of effective microorganisms, which is recommend for cabbage crops under agroecological production management.